Adolescent and young adult oncology—past, present, and future. (8th October 2019) - Close, Allison G.; Dreyzin, Alexandra; Miller, Kimberly D.; Seynnaeve, Brittani K.N.; Rapkin, Louis B.
Abstract: There are nearly 70, 000 new cancer diagnoses made annually in adolescents and young adults (AYAs) in the United States. Historically, AYA patients with cancer, aged 15 to 39 years, have not shown the same improved survival as older or younger cohorts. This article reviews the contemporary cancer incidence and survival data through 2015 for the AYA patient population based on the National Cancer Institute's Surveillance, Epidemiology, and End Results registry program and the North American Association of Central Cancer Registries. Mortality data through 2016 from the Centers for Disease Control and Prevention's National Center for Health Statistics are also described. Encouragingly, absolute and relative increases in 5‐year survival for AYA cancers have paralleled those of childhood cancers since the year 2000. There has been increasing attention to these vulnerable patients and improved partnerships and collaboration between adult and pediatric oncology; however, obstacles to the care of this population still occur at multiple levels. These vulnerabilities fall into 3 significant categories: research efforts and trial enrollment directed toward AYA malignancies, access to care and insurance coverage, and AYA‐specific psychosocial support. It is critical for providers and health care delivery systems to recognize that the AYA population remains vulnerable to provider and societal complacency.